Sinapic Acid Attenuates Cardiovascular Disorders in Rats by Modulating Reactive Oxygen Species and Angiotensin Receptor Expression. (13th July 2020) - Aldubayan, Maha A.; Ahmed, Amira S.; Emara, Ashraf M.; Ahmed, Ahmed A.; Elgharabawy, Rehab M.
Abstract : The main avoidable risk factor for cardiovascular conditions is high blood pressure (hypertension). At global level, hypertension is believed to be responsible for a 54% stroke-related mortality rate and a 47% mortality rate associated with coronary heart disease. It is postulated that sinapic acid (SA) could help in hypertension management because it displays robust antioxidant, antihyperglycemic, and peroxynitrite scavenging effects. To explore this hypothesis, this work examined the effect of SA on oxidative stress and cardiovascular disease in rats with hypertension by comparison against captopril. For this purpose, 50 male rats were used and equally allocated to five groups, namely, normal control, positive control (L-NAME), L-NAME with concomitant captopril administration, L-NAME with concomitant SA administration, and L-NAME with concomitant administration of both SA and captopril. Results showed that, by contrast to control, L-NAME exhibited marked elevation in serum CK-MB, total cholesterol, triglycerides, VLDL-C, LDL-C, Ang II, AT2R, ET-1, and angiopoietin-2; on the other hand, L-NAME exhibited marked reduction in serum HDL-C, superoxide dismutase (SOD) activity, nitric oxide synthase 3 (NOS3), and glutathione (GSH). Furthermore, joint administration of SA and captopril ameliorated hypertension, enhanced cardiovascular function, hindered hyperlipidemia, and decreased oxidative stress and myocardial hypertrophy displayed by rats with hypertension. Based on such findings, better chemopreventive or therapeutic approaches can be devised to manage hypertension and cardiovascular conditions.